Association between the Weight-Adjusted Waist Index and Serum Uric Acid: A Cross-Sectional Study - Huan Li; Guowei Fang; Chengcheng Huang; Wenrong An; Xiaohan Bai; Yanqin Huang (International Journal of Clinical Practice)
Background. Serum uric acid (SUA) was closely related to body metabolism. This study aimed to investigate the relationship between the adult weight-adjusted waist index (WWI) and SUA. Methods. In the National Health and Nutrition Examination Survey (NHANES) from 2011 to 2020, 6494 eligible participants aged ≥20  were included. The multivariate logistic regression model was used to test the correlation between WWI and SUA. At the same time, subgroup analysis was carried out by using multivariate logistic regression according to age, sex, and race. Then, the fitting smooth curve was applied to solve the association between WWI and SUA. Finally, the recursive algorithm was used to calculate the inflection point in the nonlinear relationship, and the two-stage piecewise linear regression model was used to analyze the relationship between WWI and SUA on both sides of the inflection point. Results. In all the 6494 participants, through the fully adjusted model, this study found that there was a positive correlation between WWI and SUA (β = 5.64; 95% CI: 2.62 and 8.66). In addition, this positive correlation still had certain statistical significance in the subgroup analysis stratified by sex, age, and race. Our research team found a significant positive correlation between the WWI and SUA in females, but the correlation was not significant in males. We also found a small inverted U-shaped curve between the WWI and SUA in men when we stratified the sex subgroups. The small inflection point was determined to be 11.5 cm/√ kg. In racial subgroup analysis, we also found a U-shaped relationship between the WWI and SUA in non-Hispanic White and other race/ethnicity (the inflection point was 11.08 cm/√ kg and 12.14 cm/√ kg, respectively). Conclusion. This study showed that the WWI was a newly developed and new predictor of centripetal obesity independent of body weight and there was a positive correlation between the WWI and SUA.